ADMINISTRATIVE AND LEGAL REGULATION OF THE SOCIAL AND POLITICAL SPHERE IN THE REPUBLIC OF UZBEKISTAN: CURRENT STATE AND PROSPECTS FOR DEVELOPMENT (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The article studies the peculiarities of administrative and legal regulation of social and political sphere in the Republic of Uzbekistan in the context of ongoing reforms. It analyzes the normative-legal bases of functioning of social and political institutions, mechanisms of state management in these spheres, as well as modern trends of their transformation. Special attention is paid to the role of administrative law in ensuring social rights of citizens and development of democratic institutions in the conditions of modernization of Uzbek society.